Characteristics and realization of the dividend policy of companies quoted on the Warsaw Stock Exchange for the period 2008-2017 - Jabłoński, Bartłomiej (Charakterystyka i realizacja polityki dywidend przez spółki dywidendowe notowane na Giełdzie Papierów Wartościowych w Warszawie za okres 2008-2017, 2019)
The article takes up the issue of the characteristics and the implementation of the dividend policy of companies quoted on the Warsaw Stock Exchange in Warsaw for the period 2008-2017. The purpose of the research is the characteristics of dividend policy company satisfaction mechanism, including an assessment of its actual implementation. To study the characteristics and implementation of the dividend policy by the company’s dividend, eventually it was necessary to classify the companies that during the period of 2009-2018 paid dividends for the period 2008-2017 without a break (at 31.07.2018). The test results indicate a high average annual growth rate of paid dividends. Unfortunately, more than half of the companies developed a dividend policy and those that have it as the basis for their decision on the amount of payment of dividends indicate net profit and investment needs
Financial Sciences. Nauki o Finansach, 2019, vol. 24, no. 3, s. 1-12
Keywords: dividend policy; dividens; investments; capital markets; polityka dywidend; dywidenda; inwestycje; rynki kapitałowe